The Relationships between the Myers-Briggs Type Indicator (MBTI), Job satisfaction and Well-being among Working College Students in China - Liying, Wang; Sheibani, Shahnaz (Journal of Ecohumanism, 2024)
The phenomenon of working college students is on the rise in China. Evidence elsewhere suggests that working while studying can be problematic for students' well-being. This research sought to assess whether personality types and job satisfaction can be used to prevent the decline of well-being among working college students in the country. It specifically examined the effects of Myers-Briggs Type Indicator (MBTI) types on job satisfaction and well-being, relationship between job satisfaction and well-being wellbeing, and the moderating roles of field of study and emotional state in these relationships. Based on the findings, these objectives have been successfully met. The findings show that MBTI personality types significantly shape both job satisfaction and well-being. Scoring highly on Extraversion, Sensing, Thinking, and Judging predicts high job satisfaction and better well-being among the students. Job satisfaction was also found to positively impact well-being for working students. Additionally, the findings also show that the field of study and emotional state moderate the stated relationships. The findings of this study are sound as they generally align with what other researchers have established. The findings imply that Myers-Briggs Type Indicator (MBTI) types and job satisfaction can be applied and targeted to enhance the well-being of working college students in China as the phenomenon continues to grow.